ARTISTIC WORLD OF WOMANISH PROSE - Клочек, Г. Д. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
The review of book of Tetyana Tebeshevska-Kachak «Artistic features of womanish prose of 80-90th years ХХ of item Monograph.» - Ternopil: An educational book – Bogdan, 2009. – 192с.